2016
DOI: 10.1136/bmjopen-2015-009781
|View full text |Cite
|
Sign up to set email alerts
|

What factors are important for deprescribing in Australian long-term care facilities? Perspectives of residents and health professionals

Abstract: ObjectivesPolypharmacy and multimorbidity are common in long-term care facilities (LTCFs). Reducing polypharmacy may reduce adverse events and maintain quality of life. Deprescribing refers to reducing medications after consideration of therapeutic goals, benefits and risks, and medical ethics. The objective was to use nominal group technique (NGT) to generate then rank factors that general medical practitioners (GPs), nurses, pharmacists and residents or their representatives perceive are most important when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
0
10

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(137 citation statements)
references
References 51 publications
6
121
0
10
Order By: Relevance
“…More optimistically, there was good communication between the nurses and the GPs in relation to change in BPSD and (attempts at) nonpharmacological management. This is a noted facilitating factor for appropriate prescribing in long‐term care and may have been a positive by‐product of the HALT intervention even where withdrawal was not achieved. In addition, staff could identify positive changes upon antipsychotic withdrawal such as increased alertness and improved interaction …”
Section: Discussionmentioning
confidence: 99%
“…More optimistically, there was good communication between the nurses and the GPs in relation to change in BPSD and (attempts at) nonpharmacological management. This is a noted facilitating factor for appropriate prescribing in long‐term care and may have been a positive by‐product of the HALT intervention even where withdrawal was not achieved. In addition, staff could identify positive changes upon antipsychotic withdrawal such as increased alertness and improved interaction …”
Section: Discussionmentioning
confidence: 99%
“…The questions in the current survey were therefore designed to determine the proportion of older adults with knowledge of medication harms and to assess the extent to which this knowledge is associated with initiation of a deprescribing conversation. Additionally, questions were developed to identify the sources of information that older adults use to acquire information about medication harms to determine potential barriers and optimize access to this information . An expert panel with clinical and research experience in geriatrics and deprescribing, consisting of specialist physicians, nurses, pharmacists, allied health professionals, and health researchers, reviewed the content validity of the survey questions.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies, an Australian qualitative nominal group technique study involving residents, their relatives, GPs, pharmacists and care home staff and a Canadian survey of GPs found that the most significant barriers to deprescribing in care homes were incomplete medical histories, inaccessible relatives and patients with cognitive/communication difficulties. Prescribers were reluctant to deprescribe medicines started by specialists . Interviews have not yet been conducted.…”
Section: An Investigation Into the Barriers And Facilitators To Dementioning
confidence: 99%